IMPLEMENTASI ASAS KEBEBASAN BERKONTRAK DALAM PERJANJIAN PEMBERIAN KREDIT (Studi Kasus di PT. Bank Rakyat Indonesia (Persero), Tbk. di Surakarta) - Maria Anggita Dian Pramestie; Jamal Wiwoho (Jurnal Repertorium, 2017)
AbstractThe purpose of this article is to determine implementation of freedom of contract in the agreement standards of credit at PT. Bank Rakyat Indonesia (Persero), Tbk. in Surakarta. This study is descriptive research which could be classified on socio-legal research, so it could be said that it is using non doctrinal method. The types of legal materials in this study are primary legal material, secondary one, and tertiary one. The data collection is done by interviews, focus group discussion, questioner, and documents. A systems method for this study is in interactive qualitative analysis. Result of this study had shown that the principle of freedom of contract in the agreement standards of credit is categorized in failure implementation of policy which non implementation (could not be implemented). The clauses of the agreement standards of credit at PT. Bank Rakyat Indonesia (Persero), Tbk. in Surakarta only protect PT. Bank Rakyat Indonesia (Persero), Tbk. as the creditor without pay attention to debtor’s legal rights. PT. Bank Rakyat Indonesia (Persero), Tbk. and banking institutions are expected to implement all the rules and regulations associated with the credit agreement. Enforcement of sanctions firmly by law enforcement officers against banking institutions that had violated provision of the standard clause incriminating replacement debtor so that the law can work in the community. Debtors have to read the credit agreement critically so they understand and agree with the terms before they sign it.Keywords: Freedom of Contract, Bank Credit Agreement, Standard Contract AbstrakArtikel ini bertujuan untuk mengetahui dan mengkaji implementasi asas kebebasan berkontrak dalam perjanjian pemberian kredit di PT. Bank Rakyat Indonesia (Persero), Tbk. di Surakarta. Penelitian ini termasuk penelitian hukum sosiologis atau empiris yang bersifat deskriptif. Jenis bahan hukum yang digunakan adalah bahan hukum primer, bahan hukum sekunder, dan bahan hukum tersier. Teknik pengumpulan data dilakukan dengan wawancara, focus group discussion, kuisioner, dan dokumen. Teknik analisis data menggunakan kualitatif interaktif mengalir. Berdasarkan penelitian ini diperoleh hasil bahwa asas kebebasan berkontrak dalam perjanjian pemberian kredit dikategorikan sebagai kegagalan implementasi kebijakan yang non implementation (tidak dapat diimplementasikan) yang mana klausul-klausul dalam perjanjian pemberian kredit hanya melindungi pihak PT. Bank Rakyat Indonesia (Persero), Tbk. sebagai kreditur tanpa memperhatikan hak-hak debitur. PT. Bank Rakyat Indonesia (Persero), Tbk. pada khusunya dan lembaga perbankan pada umumnya diharapkan dapat mengimplementasikan peraturan perundang-undangan terkait pembuatan perjanjian kredit tersebut di dalam praktik perbankan.Kata Kunci: Asas Kebebasan Berkontrak, Perjanjian Kredit, Perjanjian Baku